2020
DOI: 10.1002/ehf2.12890
|View full text |Cite
|
Sign up to set email alerts
|

Novel oral anticoagulant vs. warfarin in elderly atrial fibrillation patients with normal, mid‐range, and reduced left ventricular ejection fraction

Abstract: Aims Patients with concomitant atrial fibrillation (AF) and reduced left ventricular ejection fraction (LVEF) have poor prognosis. Outcomes of novel oral anticoagulant (NOAC) in elderly AF patients with normal, mid-range, and reduced LVEF were investigated. Methods and results Data were retrieved from Chang Gung Research Database during 2010-2017 for patients with AF. We excluded patients with venous thromboembolism within 6 months, total knee/hip replacement and heart valve replacement within 6 months, end-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Further Cox regression analysis showed that RMRP, age, SYNTAX score, and rest LVEF were the independent factor affecting the occurrence of MACEs. The increase of age and SYNTAX score and the decrease of resting LVEF are recognized as three indicators affecting the prognosis of patients with CAD [ 23 , 24 ]. There are few studies on the prognosis of RMRP in cardiovascular disease, but in some cancer studies, high expression of RMRP is a risk factor for poor prognosis in cancer patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further Cox regression analysis showed that RMRP, age, SYNTAX score, and rest LVEF were the independent factor affecting the occurrence of MACEs. The increase of age and SYNTAX score and the decrease of resting LVEF are recognized as three indicators affecting the prognosis of patients with CAD [ 23 , 24 ]. There are few studies on the prognosis of RMRP in cardiovascular disease, but in some cancer studies, high expression of RMRP is a risk factor for poor prognosis in cancer patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%